Long-chain omega-3 polyunsaturated fatty acids are reduced in neonates with substantial brain injury undergoing therapeutic hypothermia after hypoxic–ischemic encephalopathy - Dyall, Simon C.; Nessel, Isabell; Sharpe, Jennine A.; Yip, Ping K.; Michael-Titus, Adina T.; Shah, Divyen K. (Frontiers in Neurology, 2023)
Hypoxic–ischemic encephalopathy (HIE) is a major cause of neonatal morbidity and mortality. Although therapeutic hypothermia is an effective treatment, substantial chronic neurological impairment often persists. The long-chain omega-3 polyunsaturated fatty acids (PUFAs), docosahexaenoic (DHA) and eicosapentaenoic (EPA) acids, offer therapeutic potential in the post-acute phase. To understand how PUFAs are affected by HIE and therapeutic hypothermia we quantified for the first time the effects of HIE and therapeutic hypothermia on blood PUFA levels and lipid peroxidation. In a cross-sectional approach, blood samples from newborns with moderate to severe HIE, who underwent therapeutic hypothermia (sHIE group) were compared to samples from newborns with mild HIE, who did not receive therapeutic hypothermia, and controls. The sHIE group was stratified into cerebral MRI predictive of good (n = 10), or poor outcomes (n = 10; nine developed cerebral palsy). Cell pellets were analyzed for fatty acid content, and plasma for lipid peroxidation products, thiobarbituric acid reactive substances and 4-hydroxy-2-nonenal. Omega-3 Index (% DHA + EPA) was similar between control and HIE groups; however, with therapeutic hypothermia there were significantly lower levels in poor vs. good prognosis sHIE groups. Estimated Δ-6 desaturase activity was significantly lower in sHIE compared to mild HIE and control groups, and linoleic acid significantly increased in the sHIE group with good prognosis. Reduced long-chain omega-3 PUFAs was associated with poor outcome after HIE and therapeutic hypothermia, potentially due to decreased biosynthesis and tissue incorporation. We speculate a potential role for long-chain omega-3 PUFA interventions in addition to existing treatments to improve neurologic outcomes in sHIE.